Analisis Faktor-faktor yang Mempengaruhi Perilaku Ibu untuk Melakukan Kunjungan ANC (K4) di Wilayah Kerja Centro Saúade Comunitaria Letefoho Posto Administrativo Letefoho Municipio Ermera Timor Leste - Felisbela A. O. Oliveira (Universitas Nusa Cendana, 2019)
Antenatal Care (ANC) visit is a visit by pregnant women to health professional in order to receive ANC services. ANC visits are very important for a pregnant woman, to ensure the quality of ANCservices, there needs to be an indicator stating the visit of pregnant women with coverage of K1 and K4, where K1 is the first contact of pregnant women with health workers and K4 is the fourth contact of pregnant women or more with health workers. The purpose of this study was to determine the factors influencing maternal behavior to conduct ANC (K4) visits at Centro Saúde Comunitaria Letefoho. This research method was observational analytic with cross-sectional approach. The sample in this study consisted of 136 mothers and determined by using systematic random sampling techniques. Data were collected by using questionnaires and were analyzed by applying descriptive and bivariate using SPSS version 21. The results showed suggested that maternal education (p = 0.956), mother's knowledge (p = 0.420), mother's attitude (p = 0.817) and social culture (p = 0.618) had no association with ANC visit while the husband support (p = 0.032) and distance to health services (p = 0,000) were found to be correlated to ANC visits.